1989
DOI: 10.1016/0735-1097(89)90081-8
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection during ischemia by prior feeding with the creatine analog: Cyclocreatine

Abstract: The ability of 1-carboxymethyl-2-iminoimidazolidine (cyclocreatine), a synthetic creatine analog, to protect myocardium during global ischemia was assessed in isovolumic rat hearts using phosphorus-31 nuclear magnetic resonance spectroscopy. Wistar rats were fed a 1% cyclocreatine diet. After 2 weeks, cyclocreatine-fed (n = 8) and control (n = 7) rats were anesthetized, the heart was excised and retrograde perfusion was begun at 10 ml/min per g with 37 degrees C, phosphate-free buffer containing glucose and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…The effect of feeding Cy in the current study confirms the demonstration of its pro tective effect during ischemia shown earlier either by the delayed onset of rigor [ 1 ] or by assessing mechanical function in a perfused heart following reperfusion [5]. In all cases, loss of ATP during ischemia was slowed.…”
Section: Comparison Of Our Data With Previous Worksupporting
confidence: 75%
See 4 more Smart Citations
“…The effect of feeding Cy in the current study confirms the demonstration of its pro tective effect during ischemia shown earlier either by the delayed onset of rigor [ 1 ] or by assessing mechanical function in a perfused heart following reperfusion [5]. In all cases, loss of ATP during ischemia was slowed.…”
Section: Comparison Of Our Data With Previous Worksupporting
confidence: 75%
“…(7) no balloon was placed in the left ven tricle, and (8) hearts were allowed to beat spontaneously, not paced electrically. Fur thermore, the duration of ischemia was the same for Cy-fed and control rats in the pre vious NMR experiments [5], while in the experiments reported here, ischemia was con tinued until ATP was no longer NMR visible for all three groups of rats (CON. CR and CY).…”
Section: Comparison Of Our Data With Previous Workmentioning
confidence: 99%
See 3 more Smart Citations